Ovarian Cancer Treatment and Survival Trends Among Women Older Than 65 Years of Age in the United States, 1995–2008. Issue 1 (January 2016) - Lin, Jenny J.; Egorova, Natalia; Franco, Rebeca; Prasad-Hayes, Monica; Bickell, Nina A.
Abstract : OBJECTIVE: To evaluate whether overall survival is improving among women in the United States with advanced ovarian cancer. METHODS: This retrospective cohort study evaluated trends in treatment and overall survival for women older than 65 years diagnosed with stage III and IV epithelial ovarian cancer between 1995 and 2008 using Surveillance, Epidemiology, and End Results–Medicare data. Parametric and semiparametric multivariate survival analyses were used to assess comparative treatment survival rates and factors affecting survival and recurrence. RESULTS: Of 7, 938 women who met study criteria, 2.9% received no treatment, 15.4% underwent surgery only, 24.8% received chemotherapy only, 41.8% underwent primary debulking surgery and chemotherapy in an optimal timeframe, and 15.1% had primary debulking surgery and chemotherapy, but the timing was not optimal or patients did not complete all six cycles of chemotherapy. Those who underwent surgery only had similar survival as those who received no treatment (2.2 compared with 1.7 months), whereas those who received chemotherapy only had a better overall survival (14.4 months). Optimal treatment was associated with the longest survival time ( P <.001, median overall survival 39.0 months). Additionally, survival time associated with optimal treatment increased over the past decade. However, the proportion of women who received optimal treatment has decreased over the past decade. CONCLUSION: Elderly women with advanced ovarian cancer have the best survival with optimal therapy. When this is not offered or possible, chemotherapy alone offers better survival than surgery alone. Abstract : Elderly women with advanced ovarian cancer have the best survival with optimal therapy; chemotherapy alone offers better survival than surgery alone.